Convergence of the Newton-Type Method for Generalized Equations - Rashid, MH; Sarder, A (GANIT: Journal of Bangladesh Mathematical Society, 2016)
Let X and Y be real or complex Banach spaces. Suppose that f: X->Y is a Frechet differentiable function and F: X => 2Yis a set-valued mapping with closed graph. In the present paper, we study the Newton-type method for solving generalized equation 0 ? f(x) + F(x). We prove the existence of the sequence generated by the Newton-type method and establish local convergence of the sequence generated by this method for generalized equation. GANIT J. Bangladesh Math. Soc.Vol. 35 (2015) 27-40